Evaluación de la fabricación de tintas permanentes base agua en la empresa Pelikan Colombia S.A.S. (2019)
In this project, the partial or total replacement of solvents used in the manufacture of permanent ink is sought, in the company Pelikan Colombia S.A.S. (PCSAS). These solvents are harmful to human health and the environment, as well as being in the category of volatile organic compounds (VOCs). The implementation of water in the formulations of these inks, together with raw materials that are not restricted in national and European regulations, allows to cover international markets, which increases the competitiveness of the company, being recognized by environmentally friendly products and quality. For this reason, permanent water-based inks are chosen from the market, and analyzed to help select raw materials, among them, the acrylic resin found by Fourier transform infrared (FTIR), and dispersion pigments. Taking into account that all the substances used must be miscible in water and preferably have a basic ph. The formulation of permanent water-based inks is made by partially replacing the use of solvents in the colors red, green, black and blue. They result in adhesion to surfaces with reported values of medium to high, with a uniform and good-looking writing on glass, plastic, aluminum and ceramics. The physicochemical properties such as surface tension, pH, viscosity and solid% are within the established ranges. The production costs are attractive for the company in the creation of a new line of products with environmental input. The possibility of improving tone, appearance and adhesion on various surfaces is presented.